Pengaruh Suhu dan Ketebalan Irisan terhadap Kualitas Keripik Ubi Jalar Oranye (Ipomoea batatas L.) Menggunakan Penggorengan Vakum - Novita, Dwi Dian; Aliftama, Althoriq Rizky; Asmara, Sandi; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2025)
Processing orange sweet potato (Ipomoea batatas L.)  into chips has the potential to increase the economic value of fresh products.  The aim of this research was to study the effect of frying temperature and slice thickness on the quality parameters of orange sweet potato chips and determine the best treatment.  The test was carried out by adjusting the frying temperature at three levels (70 °C, 80 °C, and 90 °C) and the slice thickness at three levels (1 cm, 1.5 cm, and 2 cm).  The research results showed that the temperature factor had a significant effect on frying time and water content.  Meanwhile, the thickness factor has a significant effect on frying time, yield, water content and crispness.  The best treatment in this study was S2K1 (frying temperature 80 °C, slice thickness 1 cm) which produced orange sweet potato chips with a crispness score of 3.1, water content 2.77%, yield 24.89%, and frying time of 67 minutes. Keywords:  AB Mix, Fruit Waste, Liquid Organic Fertilizer, Red Spinach, SAT Hydroponics,